Peranan Keagenan dalam Penanganan Kedatangan dan Keberangkatan Kapal pada PT. Adigana Pratama Mulya Cabang Belawan - Popo Frans Pramudya Tampubolon; Dirhamsyah Dirhamsyah; Capt. Dafid Ginting (Indonesian Maritime Researchers and Lecturers, 2026)
Indonesia is known as a maritime nation, with most of its territory being water and consisting of islands. Therefore, sea transportation is crucial for connecting the islands throughout Indonesia. One such means of sea transportation is ships. Ships are a common means of communication at sea. A shipping company operates its ships from one port to another, requiring the company to manage the ships it operates at the ports they call at. This involves managing all the ship's needs, from the ship's arrival, while at the port, to its departure. The purpose of the author's observation was to determine the role of the agency in handling ship arrivals and departures at PT. Adhigana Pratama Mulya, Belawan Branch. The theoretical basis used by the author in this observation was books, the internet, laws, ministerial regulations, and other sources. The type of observation used by the author was descriptive qualitative. This observation took place at PT. Adhigana Pratama Mulya, Belawan Branch. Data sources were obtained from informants, events or activities, documents, and archives.